Boron nitride@diamond nanocrystalline epoxy resin composite material and preparation method thereof

By modifying the surface of the boron nitride nanosheets and combining them with diamond nanocrystals, boron nitride@diamond nanocrystal epoxy resin composites were prepared, which solved the problems of low thermal conductivity of the epoxy resin and poor filler compatibility, and achieved efficient thermal conductivity and improved processing performance.

CN115651364BActive Publication Date: 2025-03-07XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY

Patent Information

Application Number
CN202211432285.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-03-07
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

The existing epoxy resin has low thermal conductivity, which is difficult to meet the needs of high power density and high thermal conductivity. At the same time, the high content required when filling a single filler leads to an increase in matrix viscosity. The boron nitride nanosheets have poor compatibility with diamond nanocrystals, making it difficult to form a uniform composite material.

Method used

By modifying the surface of the boron nitride nanosheets, using dopamine hydrochloride to form modified boron nitride nanosheets, and combining them with diamond nanocrystals, boron nitride@diamond nanocrystal epoxy resin composite was prepared, and PDA@BNNS@ND filler was first prepared and then filled into the epoxy resin to solve the compatibility and dispersion problems.

Benefits of technology

The thermal conductivity of epoxy resin composite materials has been significantly improved, reaching about 17 times that of pure epoxy resin, and the thermal conductivity and processing properties of the material have been improved, interface defects have been reduced, and the overall performance of the composite materials has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115651364B_ABST
    Figure CN115651364B_ABST
Patent Text Reader

Abstract

The present invention provides a boron nitride@diamond nanocrystal epoxy resin composite material and a preparation method thereof, comprising the following steps: S1, dispersing boron nitride nanosheets in a buffer solution, adding dopamine hydrochloride, stirring and mixing at 50-60°C in the dark, and centrifuging to obtain modified boron nitride nanosheets; S2, dispersing the modified boron nitride nanosheets in water, then adding diamond nanocrystal dispersion under stirring conditions, then stirring at high speed, filtering, and obtaining diamond nanocrystal-loaded boron nitride nanosheet materials; S3, ultrasonically dispersing epoxy resin and diamond nanocrystal-loaded boron nitride nanosheet materials uniformly at 50-60°C, adding a curing agent after cooling, continuing ultrasonic dispersion, vacuum evacuating bubbles, tableting, and curing to obtain a boron nitride@diamond nanocrystal epoxy resin composite material. The present invention performs surface modification on BNNS by dopamine hydrochloride, and prepares a composite filler with ND, thereby improving the thermal conductivity of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of epoxy resin composite materials, and in particular to a boron nitride@diamond nanocrystalline epoxy resin composite material and a preparation method thereof. Background Art

[0002] At present, with the rapid development of electronics, electricity, energy and other industries, the development and application of electronic integrated circuits and electronic products have received more and more attention. With the high power density of devices and electronic products, the heat dissipation problem is becoming more and more serious. During the use of electronic equipment and devices, the operating temperature will rise due to high temperature, which seriously affects its service life and use. At present, flexible conductive insulating materials still have the problem of high thermal conductivity, good insulation and softness, which is difficult to meet the needs of the development of the power industry. Based on this point, thermal conductive insulating composite materials with high thermal conductivity and excellent insulation have broad development prospects in electronics, electricity, energy and other aspects.

[0003] Epoxy resin has been widely used in insulation casting of power equipment due to its good adhesion, insulation, corrosion resistance, low curing shrinkage, easy processing and molding, and low cost. In the heat dissipation design of electrical equipment, the thermal conductivity of epoxy resin directly affects the technical level of the entire device. However, the thermal conductivity of conventional epoxy resin is only about 0.2W / (mK), which is very low, which has a great impact on improving the heat dissipation capacity of electronic equipment. Therefore, while ensuring the electrical insulation properties of epoxy resin, its thermal conductivity is effectively improved, which is conducive to achieving the characteristics of high power density, small size, light weight, and good reliability of power devices, thereby greatly affecting the reliability and service life of the device. This is of great significance to the research of this type of thermally conductive insulating polymer materials.

[0004] At present, there are two main methods to improve the thermal conductivity of epoxy resin: one is to modify the epoxy resin matrix to obtain intrinsic epoxy resin, that is, in the synthesis and forming process of the material, adjust the structure of its molecular chain to achieve high crystallinity or orientation, and reduce phonon scattering to improve the thermal conductivity of the material; the other is to add high thermal conductivity particles to epoxy resin to make filled epoxy resin. Because the production process of intrinsic conductive epoxy resin is complex, difficult and costly, it is difficult to achieve large-scale application. At present, the method of using high thermal conductivity particles to improve its thermal conductivity has become a more common method. However, many electronic products require the coexistence of high thermal conductivity and insulation, so metal fillers cannot be added. A single filler has certain limitations on improving the thermal conductivity of epoxy resin, and at a large filling ratio, problems such as high viscosity and decreased processing performance will occur. Therefore, in order to solve the problem that the content required when using a single filler is high and the viscosity of the matrix is ​​too large, we use two different fillers for composite filling.

[0005] Commonly used thermal conductive filling materials include silicon nitride (Si3N4), boron nitride (BN), and aluminum nitride (AlN), with thermal conductivities of 180W / mK, 280W / mK, and 300W / mK, respectively. Compared with oxidants, it has high thermal conductivity and good insulation properties, and is a very important epoxy resin filling material. However, with the filling of AlN, the insulation properties of the material will be slightly reduced. For silicon nitride, the number of fillers is between 150-250 parts, and more fillers are required. BN has been widely used in electronic packaging and energy storage due to its light weight and high thermal conductivity. In addition, BN can play a role in heat dissipation, shock absorption, puncture resistance, sealing, etc. due to its high softness, high temperature resistance, thermal stability and excellent electrical insulation. It has been widely used in the manufacture of flexible TIMs and other conductive insulating materials. Due to its own corrosion resistance, BN is widely used as a thermal conductive filler in industry.

[0006] For another filler, we choose a raw material with high thermal conductivity. Commonly used thermal conductive fillers include zinc oxide (ZnO), aluminum oxide (Al2O3), boron nitride nanosheets (BNNS), and diamond nanocrystals. The thermal conductivity of zinc oxide is 30W / mK, the thermal conductivity of aluminum oxide is 33-36W / mK, the thermal conductivity of BNNS is 180W / mK, and the thermal conductivity of diamond nanocrystals is as high as 2000W / mK. By comparison, it is found that diamond nanocrystals are a very good thermal conductive material. While maintaining the excellent comprehensive properties of diamond, diamond nanocrystals also have good biocompatibility and will not cause harm to the human body; it has high transmittance and absorption rate for radar waves, ultraviolet rays, and infrared rays, and has excellent cold cathode radiation. The surface is rich in functional clusters such as carboxyl and hydroxyl groups, which can be closely combined with the surfaces of metals, rubbers, plastic polymers, fabrics, etc., and is expected to be used in machinery, electronics, chemicals, medical and other fields. In addition, due to the high temperature of diamond nanocrystals, heat diffusion can be carried out quickly. Due to its excellent thermal stability, corrosion resistance, insulation and excellent thermal conductivity, it has become a widely used thermal conductive material. Therefore, we chose boron nitride nanosheets / diamond nanocrystals as composite thermal conductive fillers.

[0007] However, when boron nitride nanosheets / diamond nanocrystals are used as composite thermal conductive materials to fill epoxy resin matrix, it is found that due to the smooth surface, low viscosity, few active groups and poor compatibility with other raw materials of boron nitride nanosheets, it is difficult for diamond nanocrystals to adhere to their surface, so the surface of boron nitride nanosheets needs to be modified. In addition, previous researchers used a co-filling method to add two or more thermal conductive fillers (that is, adding two or more fillers together to the epoxy resin matrix), and when two or more fillers are mixed, problems such as uneven dispersion or poor interface are prone to occur. Summary of the invention

[0008] In order to solve the above problems, the purpose of the present invention is to provide a boron nitride@diamond nanocrystal epoxy resin composite material and its preparation method. The method of the present invention mainly solves three problems: first, the content required when using a single filler is high, which easily causes the problem of excessive matrix viscosity; second, due to the smooth surface of boron nitride nanosheets, low viscosity, few active groups, and poor compatibility with other raw materials, it is difficult for diamond nanocrystals to adhere to their surface; third, the existing technology uses a co-filling method to add two or more thermal conductive fillers, and when two or more fillers are mixed, it is easy to cause problems such as uneven dispersion or poor interface.

[0009] To achieve the above objectives, the technical solution of the present invention is as follows.

[0010] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material comprises the following steps:

[0011] S1. Dispersing boron nitride nanosheets in a buffer solution, then adding dopamine hydrochloride, stirring and mixing at 50-60° C. in the dark to form a suspension, and centrifuging to obtain modified boron nitride nanosheets;

[0012] S2, dispersing the modified boron nitride nanosheets of S1 in water, then adding the diamond nanocrystal dispersion under stirring conditions, and then stirring at high speed and filtering to obtain diamond nanocrystal-loaded boron nitride nanosheet materials;

[0013] S3, uniformly dispersing the epoxy resin and the diamond nanocrystal-loaded boron nitride nanosheet material of S2 by ultrasonic dispersion at 50-60° C., adding a curing agent after cooling, continuing ultrasonic dispersion, and after vacuum evacuation of bubbles, tableting and curing the evacuated solution to obtain a boron nitride@diamond nanocrystal epoxy resin composite material.

[0014] Furthermore, in S1, the buffer solution is a Tris-HCl buffer solution; and the pH of the buffer solution is 8.5.

[0015] Furthermore, in S1, the mass ratio of boron nitride nanosheets to dopamine hydrochloride is 2:0.4.

[0016] Furthermore, in S2, the mass ratio of modified boron nitride nanosheets to diamond nanocrystals is 1:0.005-0.02.

[0017] Furthermore, in S2, the rotation speed of the high-speed stirring is 600-1000 r / min.

[0018] Furthermore, in S3, the mass ratio of epoxy resin to diamond nanocrystal-loaded boron nitride nanosheet material is 1:0.01-0.15.

[0019] Further, in S3, the curing agent is 593 curing agent.

[0020] Further, in S3, the specific operations of tableting and curing are as follows:

[0021] The evacuated solution was dripped onto the template, and then pressed at 70-80°C for 5-15 minutes, and then cured at 70-80°C for 2-3 hours.

[0022] The invention also provides a boron nitride@diamond nanocrystalline epoxy resin composite material.

[0023] Furthermore, the diamond nanocrystals account for 1-2% of the mass percentage of the modified boron nitride nanosheets.

[0024] Beneficial effects of the present invention:

[0025] 1. The present invention uses dopamine hydrochloride to modify the surface of BNNS, and polydopamine can be attached to the surface of BNNS. Polydopamine has extremely strong adhesion properties in a humid environment, and its molecular structure contains strong polar functional groups such as amino and hydroxyl groups. After use, it can increase the viscosity of the BNNS surface, making it easier for nanodiamonds to attach to its surface. This solves the problem that it is difficult for diamond nanocrystals to attach to the surface of boron nitride nanosheets due to their smooth surface, low viscosity, few active groups, and poor compatibility with other raw materials.

[0026] 2. Compared with the mixing method of multiple fillers co-filled in the prior art, the present invention first prepares PDA@BNNS@ND filler, and then fills the filler into epoxy resin to make a composite material, thereby alleviating the interface defects between the filler and the matrix. This solves the problem that the prior art uses a co-filling method to add two or more thermally conductive fillers, and the mixing of two or more fillers easily causes uneven dispersion or poor interface.

[0027] 3. The present invention increases the amount of ND appropriately, so that the sample prepared by the PDA@BNNS@ND composite filler is closely distributed and forms an effective heat conduction channel to a certain extent, so the thermal conductivity of the sample is relatively good. When the ND content is 1%, the thermal conductivity reaches the highest, which is 3.5w / (m·k), which is about 17 times that of pure epoxy resin.

[0028] 4. The present invention utilizes the functional group at one end of PDA (polydopamine) to produce a certain reaction with the epoxy resin matrix, thereby enhancing the interface bonding between the epoxy resin matrix and the filler, reducing the defects of the interface, and thus improving the thermal conductivity of the composite material. Therefore, when the content of the composite filler (PDA@BNNS@ND) is 7%, the thermal conductivity of the epoxy resin composite material reaches the maximum, which is about 20 times that of pure EP (epoxy resin). BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM images of the products obtained in Examples 1 to 3 of the present invention and Comparative Example 1. (A) is the SEM image of Comparative Example 1 in which BNNS is not modified and ND is added. (B), (C), and (D) are SEM images of BNNS with surface modification and different ND contents added.

[0030] Figure 2 The TEM images of the products obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in Figure 1. (a) is a TEM image of Comparative Example 1 in which BNNS is not modified and ND is not added. (b), (c), and (d) are TEM images of BNNS with surface modification and different ND contents added.

[0031] Figure 3 : is a SEM image of the boron nitride@diamond nanocrystalline epoxy resin composite material prepared in Example 1 of the present invention. Figure 3 (b) Yes Figure 3 (a) Enlarged view of the framed part.

[0032] Figure 4 These are SEM images of composite materials with different ND contents added in Examples 2 to 3 of the present invention, wherein (A) is a SEM image of an epoxy resin composite material with 0.5% ND content prepared in Example 2; and (B) is a SEM image of an epoxy resin composite material with 2.0% ND content prepared in Example 3.

[0033] Figure 5 The figures are comparative bar graphs of thermal diffusivity and thermal conductivity of epoxy resin composite materials prepared with different filler contents and ND contents in Examples 1 to 7 and Comparative Examples 1 to 2. Among them, (a) is a comparative bar graph of thermal diffusivity and thermal conductivity of epoxy resin composite materials with different filler contents in Examples 1 and 4 to 7. (b) is a comparative bar graph of thermal diffusivity and thermal conductivity of epoxy resin composite materials with different ND contents in Examples 1 to 3 and Comparative Example 2. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0036] In the following embodiments of the present invention, Tris is trishydroxymethylaminomethane; BNNS is boron nitride nanosheets; PDA is polydopamine; and ND is diamond nanocrystals.

[0037] Unless otherwise specified, the methods described in the following examples are all conventional methods; the reagents and materials described are all commercially available unless otherwise specified.

[0038] Example 1

[0039] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material comprises the following steps:

[0040] S1. Prepare Tris-HCl buffer solution with pH = 8.5

[0041] Tris was dissolved in deionized water to prepare a Tris solution with a concentration of 0.012 g / mL; HCl was dissolved in deionized water to prepare a HCl solution with a concentration of 0.008 g / mL.

[0042] The Tris solution and the HCl solution were mixed in a volume ratio of 10 mL:3 mL, and deionized water was added to prepare a Tris-HCl buffer solution with a pH of 8.5.

[0043] S2. Preparation of modified boron nitride nanosheets

[0044] 2 g of BNNS particles were added to 200 mL of Tris-HCl buffer solution and dispersed evenly by water bath sonication for 5 min. Then, 0.4 g of dopamine hydrochloride was added to the mixture. The suspension was stirred for 24 h using a magnetic stirrer at 60 °C and protected from light. The color of the suspension changed from white to gray and finally to brown-black.

[0045] The reaction suspension was then divided into several centrifuge tubes, anhydrous ethanol was added and mixed and shaken to remove unreacted dopamine hydrochloride, and the suspension was placed in a high-speed centrifuge and centrifuged at 4000r / min for 30min. The precipitate in the centrifuge tube was collected, which was the modified boron nitride nanosheets; the collected modified boron nitride nanosheets were dispersed with ethanol and centrifuged again, and this cycle was repeated three times; brown-black particles were obtained after centrifugation, and placed in a 60°C oven for vacuum drying for 24h to obtain the hybrid filler product PDA@BNNS.

[0046] S3. Preparation of diamond nanocrystal-loaded boron nitride nanosheet materials

[0047] 1 g of PDA@BNNS powder was weighed and added into 200 mL of deionized water, and then dispersed evenly by water bath ultrasound to obtain a PDA@BNNS dispersion with a concentration of 0.005 g / mL.

[0048] 0.01 g of ND was weighed and added into 20 mL of deionized water, and dispersed evenly by water bath ultrasonication to obtain a ND dispersion with a concentration of 0.0005 g / mL.

[0049] 20 mL of ND dispersion was added dropwise to 200 mL of PDA@BNNS dispersion. During the addition process, magnetic stirring was performed at a speed of 400 rpm / min. After the addition was completed, high-speed stirring was performed for 30 minutes at a speed of 600 rpm / min. The solution after high-speed stirring was then filtered to obtain ND-loaded BNNS powder, which was then dried at 60°C for 24 hours to obtain the filler product PDA@BNNS@ND.

[0050] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0051] Weigh 1g of bisphenol A epoxy resin, add 0.0994g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0052] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0053] Example 2

[0054] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0055] S3. Preparation of diamond nanocrystal-loaded boron nitride nanosheet materials

[0056] 1 g of PDA@BNNS powder was weighed and added into 200 mL of deionized water, and then dispersed evenly by water bath ultrasound to obtain a PDA@BNNS dispersion with a concentration of 0.005 g / mL.

[0057] 0.005 g of ND was weighed and added into 20 mL of deionized water, and dispersed evenly by water bath sonication to obtain a ND dispersion with a concentration of 0.00025 g / mL.

[0058] 20 mL of ND dispersion was added dropwise to 200 mL of PDA@BNNS dispersion. During the addition process, magnetic stirring was performed at a speed of 400 rpm / min. After the addition was completed, high-speed stirring was performed for 30 minutes at a speed of 600 rpm / min. The solution after high-speed stirring was then filtered to obtain ND-loaded BNNS powder, which was then dried at 60°C for 24 hours to obtain the filler product PDA@BNNS@ND.

[0059] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0060] Weigh 1g of bisphenol A epoxy resin, add 0.0994g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0061] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0062] Example 3

[0063] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0064] S3. Preparation of diamond nanocrystal-loaded boron nitride nanosheet materials

[0065] 1 g of PDA@BNNS powder was weighed and added into 200 mL of deionized water, and then dispersed evenly by water bath ultrasound to obtain a PDA@BNNS dispersion with a concentration of 0.005 g / mL.

[0066] 0.02 g of ND was weighed and added into 20 mL of deionized water, and dispersed evenly by water bath ultrasonication to obtain a ND dispersion with a concentration of 0.001 g / mL.

[0067] 20 mL of ND dispersion was added dropwise to 200 mL of PDA@BNNS dispersion. During the addition process, magnetic stirring was performed at a speed of 400 rpm / min. After the addition was completed, high-speed stirring was performed for 30 minutes at a speed of 600 rpm / min. The solution after high-speed stirring was then filtered to obtain ND-loaded BNNS powder, which was then dried at 60°C for 24 hours to obtain the filler product PDA@BNNS@ND.

[0068] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0069] Weigh 1g of bisphenol A epoxy resin, add 0.0994g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0070] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0071] Example 4

[0072] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0073] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0074] Weigh 1g of bisphenol A epoxy resin, add 0.013g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0075] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0076] Example 5

[0077] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0078] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0079] Weigh 1g of bisphenol A epoxy resin, add 0.041g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0080] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0081] Example 6

[0082] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0083] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0084] Weigh 1g of bisphenol A epoxy resin, add 0.0695g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0085] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0086] Example 7

[0087] A method for preparing a boron nitride@diamond nanocrystalline epoxy resin composite material is basically the same as the method in Example 1, except that:

[0088] S4. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0089] Weigh 1g of bisphenol A epoxy resin, add 0.1467g of PDA@BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0090] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS@ND.

[0091] Comparative Example 1

[0092] A method for preparing a boron nitride@diamond nanocrystal epoxy resin composite material is basically the same as the method in Example 1, except that the BNNS is not modified. The specific method comprises the following steps:

[0093] S1. Prepare Tris-HCl buffer solution with pH = 8.5

[0094] Tris was dissolved in deionized water to prepare a Tris solution with a concentration of 0.012 g / mL; HCl was dissolved in deionized water to prepare a HCl solution with a concentration of 0.008 g / mL.

[0095] The Tris solution and the HCl solution were mixed in a volume ratio of 10 mL:3 mL, and deionized water was added to prepare a Tris-HCl buffer solution with a pH of 8.5.

[0096] S2. Preparation of diamond nanocrystal-loaded boron nitride nanosheet materials

[0097] 1 g of BNNS powder was weighed and added into 200 mL of deionized water, and dispersed evenly by water bath ultrasound to obtain a BNNS dispersion with a concentration of 0.005 g / mL.

[0098] 0.01 g of ND was weighed and added into 20 mL of deionized water, and dispersed evenly by water bath ultrasonication to obtain a ND dispersion with a concentration of 0.0005 g / mL.

[0099] 20 mL of ND dispersion was added dropwise to 200 mL of BNNS dispersion. During the addition process, magnetic stirring was performed at a speed of 400 rpm / min. After the addition was completed, high-speed stirring was performed for 30 minutes at a speed of 600 rpm / min. The solution after high-speed stirring was then filtered to obtain ND-loaded BNNS powder, which was then dried at 60°C for 24 hours to obtain the filler product BNNS@ND.

[0100] S3. Preparation of boron nitride@diamond nanocrystalline epoxy resin composites

[0101] Weigh 1g of bisphenol A epoxy resin, add 0.0994g of BNNS@ND, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0102] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with BNNS@ND.

[0103] Comparative Example 2

[0104] A method for preparing a boron nitride@diamond nanocrystal epoxy resin composite material is substantially the same as the method in Example 1, except that ND is not added.

[0105] S3. Preparation of diamond nanocrystal-loaded boron nitride nanosheet materials

[0106] 1 g of PDA@BNNS powder was weighed and added into 200 mL of deionized water, and then dispersed evenly by water bath ultrasound to obtain a PDA@BNNS dispersion with a concentration of 0.005 g / mL.

[0107] 20 mL of deionized water was added dropwise to 200 mL of PDA@BNNS dispersion. During the addition process, magnetic stirring was performed at a speed of 400 rpm / min. After the addition was completed, high-speed stirring was performed for 30 minutes at a speed of 600 rpm / min. The solution after high-speed stirring was then filtered to obtain BNNS powder, which was then dried at 60°C for 24 hours to obtain the filler product PDA@BNNS.

[0108] S4. Preparation of boron nitride epoxy resin composite material

[0109] Weigh 1g of bisphenol A epoxy resin, add 0.0994g of PDA@BNNS, and perform ultrasonic treatment in a water bath at 60°C for 15min to evenly disperse the composite filler in the epoxy resin. After cooling to room temperature, add 0.2g of 593 curing agent, stir with a glass rod, and perform ultrasonic treatment in a water bath at room temperature for 5min to evenly disperse the curing agent.

[0110] Then, the bubbles were extracted in a vacuum box at room temperature (Note: the bubble extraction time should not be too long, otherwise the solution will solidify). The solution with the bubbles extracted was dripped on a 10×10 cm template engraved in advance, pressed with two 10-micron copper foils, and pressed at 80°C for about 10 minutes. After that, it was cured in a drying oven at 80°C for 3 hours with a glass sheet to obtain a thermally conductive insulating epoxy resin film filled with PDA@BNNS.

[0111] The performance of the products obtained in Examples 1 to 7 and Comparative Examples 1 to 2 was tested below.

[0112] 1. The comparison results of raw material dosage for preparing epoxy resin composite materials with different ND contents and different filler contents are shown in Tables 1 and 2.

[0113] Table 1 Raw material dosage for preparing epoxy resin composites with different ND contents

[0114] raw material PDA@BNNS ND ND content Example 1 1g 0.01g 1% Example 2 1g 0.005g 0.5% Example 3 1g 0.02g 2% Comparative Example 2 1g - 0

[0115] Table 2 Raw material dosage for preparing epoxy resin composites with different filler contents

[0116]

[0117]

[0118] Note: The epoxy resin and curing agent without filler are used as blank comparison. “-” means no filler is added.

[0119] 2. The surface conditions of epoxy resin composites prepared by modified BNNS and unmodified BNNS with ND added were observed using SEM / TEM analysis to determine the effect of BNNS modification on the loading of ND in the epoxy resin matrix.

[0120] Figure 1 and Figure 2 The SEM and TEM images of the products obtained in Examples 1 to 3 and Comparative Example 1 are shown respectively. Figure 1 (A) and Figure 2 (a) SEM and TEM images of Example 1 in which BNNS was not modified but ND was added. Figure 1 (B)(C)(D), Figure 2 (b)(c)(d) are SEM and TEM images of BNNS with surface modification and different ND contents added.

[0121] Figure 1 (A) and Figure 2 (a) is the SEM and TEM images of BNNS without modification and addition of ND. Figure 1 (A) and Figure 2 (a) It can be seen that the microstructure of boron nitride (BN) is very thin and flaky, and the surface is relatively smooth, and ND is not successfully attached.

[0122] Figure 1 (B) Figure 1 (C) Figure 1 (D) Figure 2 (b) Figure 2 (c) and Figure 2 (d) The surface of BNNS was modified. After adding diamond, large flakes of BN and small particles of ND were staggered and alternating. As the content of ND increased, the amount of ND attached to BNNS also increased, indicating that the PDA@BNNS@ND filler was successfully prepared. It can be concluded that by modifying the surface of BNNS with dopamine hydrochloride, polydopamine can be attached to the surface of BNNS. Polydopamine has extremely strong adhesion properties in a humid environment, and its molecular structure contains strong polar functional groups such as amino and hydroxyl groups. After use, it increases the viscosity of the BNNS surface, making it easier for nanodiamonds to attach to its surface.

[0123] 3. The fracture cross-section of the epoxy resin composite material was observed using a scanning electron microscope to intuitively observe the orientation of BNNS@ND in the epoxy resin matrix.

[0124] Figure 3 is a SEM image of the boron nitride@diamond nanocrystalline epoxy resin composite material prepared in Example 1. Figure 3 (b) Yes Figure 3 (a) Enlarged view of the framed part.

[0125] Figure 3 The selected observation section is the cross section of the composite material perpendicular to the orientation direction of the filler. If the filler is well oriented in the composite material, most of the fillers seen in the SEM image should be horizontal. Figure 3 It can be seen that most of the fillers are evenly dispersed in the epoxy resin matrix, and they show a highly consistent orientation state in the lateral direction, and the orientation structure of the fillers in the composite material is very significant. This shows that compared with the mixing method of multiple fillers co-filled in the prior art, Example 1 of the present invention first prepares PDA@BNNS@ND, and then fills the filler into the epoxy resin to make a composite material, thereby alleviating the interface defects between the filler and the matrix.

[0126] 4. The fracture cross-sections of epoxy resin composites with different ND contents were observed using a scanning electron microscope to intuitively observe the orientation of fillers with different ND contents in the epoxy resin matrix.

[0127] Figure 4 1 and 2 are SEM images of composite materials with different ND contents, wherein (A) is a SEM image of the epoxy resin composite material with 0.5% ND content prepared in Example 2; (B) is a SEM image of the epoxy resin composite material with 2.0% ND content prepared in Example 3.

[0128] Depend on Figure 4 It can be seen that when the content of diamond nanocrystals (ND) is low, the distribution of the material is relatively loose and cannot form a good heat conduction path. As the amount of ND increases, the sample prepared by PDA@BNNS@ND composite filler is closely distributed and forms an effective heat conduction channel to a certain extent, so the thermal conductivity of the sample is relatively good.

[0129] 5. The thermal diffusivity and thermal conductivity of epoxy resin composites prepared with different filler contents and ND contents were tested to determine the effects of filler content and ND content on the thermal diffusivity and thermal conductivity of the composites.

[0130] Figure 5 It is a comparative bar graph of thermal diffusivity and thermal conductivity of epoxy resin composites prepared with different filler contents and ND contents. Figure 5 (a) is a comparative bar graph of thermal diffusivity and thermal conductivity of epoxy resin composite materials with different filler contents; wherein 0, 1, 3, 5, 7, and 10 represent the blank control, Example 4, Example 5, Example 6, Example 1, and Example 7 in Table 2, respectively. Figure 5(b) is a comparative bar chart of thermal diffusivity and thermal conductivity of epoxy resin composite materials with different ND contents; wherein 0.0, 0.5, 1.0, and 2.0 represent Comparative Example 2, Example 2, Example 1, and Example 3 in Table 1, respectively.

[0131] In order to further improve the thermal conductivity of the epoxy resin composite material, Examples 1 to 7 of the present invention added diamond nanocrystals on the surface of the thermally conductive filler BNNS to prepare a new type of thermally conductive composite filler (PDA@BNNS@ND), and filled it into the epoxy resin matrix to prepare the epoxy resin composite material.

[0132] The thermal diffusivity and thermal conductivity of the epoxy resin composite materials of Examples 1 to 7 and Comparative Examples 1 to 2 are as follows: Figure 5 As shown. Figure 5 (a) It can be seen that the thermal conductivity of the epoxy resin composite material continues to increase with the increase of PDA@BNNS@ND content. It reaches the maximum when the composite filler content is 7%, which is about 20 times that of pure EP (epoxy resin). The main reason is that the functional group at one end of PDA (polydopamine) reacts with the epoxy resin matrix, which enhances the interface bonding between the epoxy resin matrix and the filler, reduces the defects of the interface, and thus improves the thermal conductivity of the composite material. However, when the content of PDA@BNNS@ND is greater than 7%, the thermal conductivity of the composite material begins to decrease slightly when the filler content is further increased. The main reason is that in the high addition state (PDA@BNNS@ND content>7%), the thermal conductive filler is difficult to disperse evenly inside the epoxy resin, the fillers are in too close contact, and the interface defects between the thermal conductive filler and the epoxy resin matrix become more serious, resulting in the gradual increase of scattering at the interface during the propagation of phonons, thereby hindering the improvement of the thermal conductivity of the composite material. In general, the thermal conductivity of the composite material shows a trend of first increasing and then decreasing with the increase of the thermal conductive filler content.

[0133] Depend on Figure 5 (b) It can be clearly seen that with the increase of ND content, the thermal conductivity of the composite material increases first and then decreases. The thermal conductivity reaches the highest at 1% content, which is 3.5w / (m·k), which is about 17 times that of pure epoxy resin. This is because the dispersion of ND in the filler is not good. When the content is large, its agglomeration increases, the gaps in the composite material become smaller, and the interface defects increase, which causes the thermal conductivity to weaken.

[0134] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a boron nitride@diamond nanocrystal epoxy resin composite material, characterized in that: The following steps are involved: S1. Dispersing boron nitride nanosheets in a buffer solution, then adding dopamine hydrochloride, stirring and mixing at 50-60° C. in the dark to form a suspension, and centrifuging to obtain modified boron nitride nanosheets; S2, dispersing the modified boron nitride nanosheets of S1 in water, then adding diamond nanocrystal dispersion under stirring conditions, stirring at high speed, filtering, and obtaining diamond nanocrystal-loaded boron nitride nanosheet materials; the mass ratio of the modified boron nitride nanosheets to the diamond nanocrystals is 1:0.005-0.02; S3. Ultrasonically disperse the epoxy resin and the diamond nanocrystal-loaded boron nitride nanosheet material of S2 at 50-60° C., add a curing agent after cooling, continue ultrasonic dispersion, and after vacuum evacuation of bubbles, press and solidify the evacuated solution to obtain a boron nitride@diamond nanocrystal-loaded boron nitride nanosheet material; the mass ratio of epoxy resin to diamond nanocrystal-loaded boron nitride nanosheet material is 1:0.01-0.

15.

2. The method for preparing the boron nitride@diamond nanocrystal epoxy resin composite material according to claim 1, characterized in that: In S1, the buffer solution is a Tris-HCl buffer solution; the pH of the buffer solution is 8.

5.

3. The method for preparing the boron nitride@diamond nanocrystal epoxy resin composite material according to claim 1, characterized in that: In S1, the mass ratio of boron nitride nanosheets to dopamine hydrochloride is 2:0.

4.

4. The method for preparing the boron nitride@diamond nanocrystal epoxy resin composite material according to claim 1, characterized in that: In S2, the rotation speed of the high-speed stirring is 600-1000 r / min.

5. The method for preparing the boron nitride@diamond nanocrystal epoxy resin composite material according to claim 1, characterized in that: In S3, the curing agent is 593 curing agent.

6. The method for preparing the boron nitride@diamond nanocrystal epoxy resin composite material according to claim 1, characterized in that: In S3, the specific operations of tableting and curing are as follows: The evacuated solution was dripped onto the template, and then pressed at 70-80°C for 5-15 minutes, and then cured at 70-80°C for 2-3 hours.

7. A boron nitride@diamond nanocrystalline epoxy resin composite material prepared by the method described in any one of claims 1 to 6.

8. The boron nitride@diamond nanocrystalline epoxy resin composite material according to claim 7, characterized in that: The diamond nanocrystals account for 1-2% of the mass percentage of the modified boron nitride nanosheets.

Citation Information

Patent Citations

  • Preparation method of dopamine modified boron nitride composite material with high thermal conductivity

    CN111057347A

  • Tough high-thermal-conductivity film and preparation method thereof

    CN114644908A

Cited By

  • Heat-conducting gasket with core-shell structure and preparation method of heat-conducting gasket

    CN122060330A